(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
The list of bryophyte species from alpine shrubby formations in Gorgany Mts is based on my field records and literature data. In the mountain pine communities, 39 species were identified (28 mosses, 11 liverworts). A thick moss cover is often developed in pine communities. In communities with Alnus viridis, 35 species were found. Moss cover in alder vegetation is thinner and less developed.